2020
DOI: 10.1007/s00277-020-04249-2
|View full text |Cite
|
Sign up to set email alerts
|

Biological properties of bone marrow plasma cells influence their recovery in aspirate specimens: impact on classification of plasma cell disorders and potential bias to evaluation of treatment response

Abstract: Methods to estimate bone marrow plasma cells (BMPC) basically include histopathology, cytomorphology, and flow cytometry. The present study compares the outcomes of these methods with special focus on the impact of BMPC-specific characteristics on their recovery by either method. Laboratory reports of diagnostic samples from 238 consecutive patients with suspected or known plasma cell disease were retrospectively analyzed. The median (IQR) proportion of BMPC was 30.0% (15.0–70.0%) by histological review (hBMPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Many studies (Supplement Table 4) have shown similar results where PC recovery on flow cytometry is affected by the quality of specimen, but a proportion of PC recovery has also been attributed to processing and biological properties of the disease 5,6,7,11,19–21 . Our results demonstrate that the recovery of PCs on flow cytometry was significantly reduced with increasing PC% on second pull smear ( p < 0.001) and in NDMM ( p < 0.001) than in FCMI (Table 3).…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Many studies (Supplement Table 4) have shown similar results where PC recovery on flow cytometry is affected by the quality of specimen, but a proportion of PC recovery has also been attributed to processing and biological properties of the disease 5,6,7,11,19–21 . Our results demonstrate that the recovery of PCs on flow cytometry was significantly reduced with increasing PC% on second pull smear ( p < 0.001) and in NDMM ( p < 0.001) than in FCMI (Table 3).…”
Section: Discussionsupporting
confidence: 73%
“…BMPC% plays a key role not only in disease classification of MM, but also aids in assessing response to therapy. BMPC% assessed on different samples are known to be different and, hence it is recommended to use higher PC value (wherever available) for assigning diagnosis and assessing treatment response in cases of MM 11 . In our study, we demonstrated that the aspirate sample obtained from two different pulls if used to determine BMPC%, will yield divergent results.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations